Genetic variants at the EGLN1 locus associated with high‐altitude adaptation in Tibetans are absent or found at low frequency in highland Andeans. (4th February 2019) - Heinrich, Erica C.; Wu, Lu; Lawrence, Elijah S.; Cole, Amy M.; Anza‐Ramirez, Cecilia; Villafuerte, Francisco C.; Simonson, Tatum S.
Abstract: EGLN1 encodes the hypoxia‐inducible factor (HIF) pathway prolyl hydroxylase 2 (PHD2) that serves as an oxygen‐sensitive regulator of HIF activity. The EGLN1 locus exhibits a signature of positive selection in Tibetan and Andean populations and is associated with hemoglobin concentration in Tibetans. Recent reports provide evidence for functional roles of protein‐coding variants within the first exon of EGLN1 (rs186996510, rs12097901) that are linked to an adaptive signal in Tibetans, yet whether these same variants are present and contribute to adaptation in Andean highlanders is unknown. We determined the frequencies of these adaptive Tibetan alleles in Quechua Andeans resident at high altitude (4, 350 m) in addition to individuals of Nepali ancestry resident at sea level. The rs186996510 C (minor) allele previously found at high frequency in Tibetans is absent in Andean (G: 100%) and rare among Nepali (C: 11.8%, G: 88.2%) cohorts. The minor G allele of rs12097901 is found at similarly low frequencies in Andeans (G: 12.7%, C: 87.3%) and Nepalis (G: 23.5%, C: 76.5%) compared to Tibetans. These results suggest that adaptation involving EGLN1 in Andeans involves different mechanisms than those described in Tibetans. The precise Andean adaptive variants remain to be determined.